2021
DOI: 10.1002/lio2.610
|View full text |Cite
|
Sign up to set email alerts
|

Low physical activity in patients diagnosed with head and neck cancer

Abstract: Background This pilot study aimed to describe physical activity (PA) and self‐perceived function, health and quality of life (QoL) prior to oncological treatment in patients with head and neck cancer (HNC). Methods In a prospective study including 49 patients, self‐perceived PA (Saltin‐Grimby scale) and health‐related QoL (European Organization for Research and Treatment of Cancer Quality of Life questionnaire Core 30 and EQ‐5D) were assessed. Further, PA was also measured by an accelerometer attached to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
(84 reference statements)
2
10
0
Order By: Relevance
“…Low levels of physical activity were observed in the present study. Similarly low levels have been reported in previous studies for HaNC survivors in the United States (Rogers et al, 2006), Netherlands (Douma et al, 2020) and Sweden (Karczewska‐Lindinger et al, 2021). Moreover, the physical activity levels of HaNC survivors have been found to be significantly lower post‐treatment compared to pre‐treatment (Sammut et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Low levels of physical activity were observed in the present study. Similarly low levels have been reported in previous studies for HaNC survivors in the United States (Rogers et al, 2006), Netherlands (Douma et al, 2020) and Sweden (Karczewska‐Lindinger et al, 2021). Moreover, the physical activity levels of HaNC survivors have been found to be significantly lower post‐treatment compared to pre‐treatment (Sammut et al, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Similarly low levels have been reported in previous studies for HaNC survivors in the United States (Rogers et al, 2006), Netherlands (Douma et al, 2020) and Sweden (Karczewska-Lindinger et al, 2021).…”
Section: Physical Activity Levelssupporting
confidence: 88%
“…Large deviations between self‐reported levels and levels obtained by more objective methods have been demonstrated, with both overestimation and underestimation, in members of the general population and in a HNC cohort 5,14,15 . Among patients with HNC, only few studies have used more objective assessment of PA, using an accelerometer 2,3 . Assessment of PA with an accelerometer has a stronger association with measures of cardiovascular disease than self‐reported PA as measured in a general population 16 …”
Section: Introductionmentioning
confidence: 99%
“…Patients diagnosed with HNC have a lower level of physical activity (PA) compared to a healthy population around the same age 1–3 ; one study reported that only 8.5% of the patients with HNC reached the recommended levels of exercise post‐treatment 1 as written in current public health guidelines, compared to 72% of the adult population globally 4 . Low levels of PA before HNC treatment have also been observed 3,5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation